Capsaicin and Quercitrin Maintained Lipid Homeostasis of Hyperlipidemic Mice: Serum Metabolomics and Signaling Pathways - Yanxia Wu; Weihua Liu; Rongrong Wang; Yunhe Lian; Xinying Cheng; Ruili Yang; Xianghong Wang; Si Mi (Foods)
Capsaicin and quercitrin have proved to be two major ingredients in fresh chili pepper. However, the effect of these two compounds on hyperlipidemia and the related molecular mechanisms were still unclear. This work was performed to examine the hypolipidemic capacity of capsaicin and quercitrin as well as the related signaling pathways. Hyperlipidemia was induced in mice by feeding them with a high-fat diet for 4 weeks. Both capsaicin and quercitrin were beneficial to inhibit a rise in fasting glucose, total cholesterol, total triglycerides, low-density lipoprotein cholesterol, and total bile acids and to lift the level of high-density lipoprotein cholesterol in the serum. The optimal lipid-lowering data were achieved in the capsaicin and quercitrin/3:1 group. Supplementation with capsaicin and quercitrin both singly and together in the feed caused a significant influence on the metabolite profiles of mouse serum. The signaling pathway for the hypolipidemic effect of capsaicin and quercitrin was related to the down-regulation of epidermal growth factor receptor (EGFR) but the up-regulation of phosphatidylin-ositol-3-kinase (PI3K), protein kinase Bb(Akt), farnesoid X receptor 1 (FXR1), and cholesterol 7α-hydroxylase (CYP7A1). This study confirmed the jointly hypolipidemic effect of capsaicin and quercitrin, which would benefit the valorization of chili pepper resources.